Field assay using a native entomopathogenic nematode for biological control of the weevil Phyrdenus muriceus in organic eggplant crops in Argentina - Eliceche, Daiana Pamela (2020)
The weevil Phyrdenus muriceus Germar (Coleoptera: Curculionidae) is an emergent pest of eggplant (Solanum melongena L.) crops in the humid Pampa of Argentina. Entomopathogenic nematodes (EPNs) constitute an effective and environmentally safe strategy within integrated pest management. The efficacy of a native EPN Heterorhabditis bacterio- phora SUP isolate for the control of P. muriceus was evaluated. Larvae and adults were susceptible to the nematode in laboratory assays. Field evaluations indicated a slight reduction of P. muriceus popula- tions, evidenced after a second application by a decrease of the foliar damage in the eggplant crops. Adults of P. muriceus parasitized by H. bacteriophora were observed in the field one month after the second application.